2007
DOI: 10.1111/j.1740-8709.2007.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding patterns of underweight children in rural Malawi given supplementary fortified spread at home

Abstract: Fortified spread (FS), containing dry food particles embedded in edible fat, offers a convenient means for nutrition rehabilitation. To describe how caregivers feed FS to their undernourished children at home, and how FS use affects other feeding patterns, we conducted a longitudinal observational study in rural Malawi. Sixteen 6- to 17-month-old underweight children (weight-for-age z-score < -2.0; -3.0 < weight-for-height z-score < 0) received FS for 12 weeks. Twelve-hour observations were conducted before su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
4
26
2
Order By: Relevance
“…In Niger, the perception of RUSF as a medicine or food was higher than in Malawi, where RUSF was mostly considered a food by caregivers. However, feeding patterns and behaviors related to RUSF consumption were also similar to those reported in previous studies (Flax et al, 2008(Flax et al, , 2010Galpin et al, 2007), adding further evidence that RUSF can be incorporated into the daily diets of children in different contexts without having a negative impact on other feeding habits like breastfeeding. Respondents in our study reported high levels of social pressures: the fear of negative consequences for the entire community if one caregiver does not follow the instructions was highlighted in several districts.…”
Section: Discussionsupporting
confidence: 83%
“…In Niger, the perception of RUSF as a medicine or food was higher than in Malawi, where RUSF was mostly considered a food by caregivers. However, feeding patterns and behaviors related to RUSF consumption were also similar to those reported in previous studies (Flax et al, 2008(Flax et al, , 2010Galpin et al, 2007), adding further evidence that RUSF can be incorporated into the daily diets of children in different contexts without having a negative impact on other feeding habits like breastfeeding. Respondents in our study reported high levels of social pressures: the fear of negative consequences for the entire community if one caregiver does not follow the instructions was highlighted in several districts.…”
Section: Discussionsupporting
confidence: 83%
“…This may have led to incomplete consumption and sharing with family members of the supplement more frequently among participants who were given CSB. Whereas the parents in our study typically reported no diversion of the supplement to unintended beneficiaries, earlier studies suggest sharing of both CSB and LNS, but this seems to occur more often with porridges (23). Additionally, due to its volume, CSB may not be a true supplement, because it likely displaces other home foods.…”
Section: Discussionmentioning
confidence: 67%
“…, ), while other parts looked at social and cultural aspects of infant and young child feeding (Flax et al . , ). The overall goal of the ethnographic research described here was to provide information that could be used to design malnutrition prevention and treatment programmes in southern Malawi that build upon existing cultural models of care rather than simply identifying ways of changing local beliefs to fit with biomedical models.…”
Section: Introductionmentioning
confidence: 99%